Tingkat Kesesuaian Penyusunan Rencana Kerja Perangkat Daerah Berdasarkan Permendagri Nomor 86 Tahun 2017 - Hosnan Efendi; Mohammad Natsir (Policy and Maritime Review, 2023)
Consistency between Regional Development Planning policies is carried out through verification of Development Plan Documents at the Regional Apparatus level. Verification of the documents in question is carried out on the Preliminary Draft and Final Draft of the Regional Apparatus Work Plan which is integrated with the RKPD preparation stages. This research aims to describe and analyze the level of suitability of the substance of the Regional Apparatus Work Plan based on Minister of Home Affairs Regulation Number 86 of 2017 as well as the formulation of strategies to improve the suitability of the Regional Apparatus Work Plan. The research method used was a qualitative approach, by conducting observations and interviews with the Head of Division and Functional Planners at Bappeda R&D as well as Functional Planners at Regional Apparatus within the Economic Sector. The results of the analysis of the qualitative data that have been collected show that of the 5 (five) Regional Apparatuses in the Economic Sector scope of the Probolinggo City R&D Bappeda, there is only 1 (one) Regional Apparatus that has a high level of conformity, namely DKPPP of 85.71%, while 4 ( four) Other Regional Apparatus have low compliance levels below 50%. This cannot be separated from several obstacles/problems faced by Regional Apparatus in preparing Renja PD, including the lack of commitment from Regional Apparatus, limited time in preparing Renja PD, lack of understanding by Regional Apparatus regarding the substance of preparing Renja PD in accordance with Permendagri Number 86 2017 and the lack of communication and coordination within the regional apparatus.